2022 Western Kansas Agricultural Research Report (Kansas Agricultural Experiment Station Research Reports, 2022)
Summary of research conducted at western Kansas research stations, including Hays, Garden City, Tribune, and Colby. Topics include corn, cropping and tillage systems, insect control, irrigation, management practices, weather, weed science, and wheat.
Keywords: western Kansas research; crops; irrigation; dryland; weed management; insect control; weather